Insecticide susceptibility status of Anopheles gambiae (s.l.) in South-West Cameroon four years after long-lasting insecticidal net mass distribution - Boussougou-Sambe, Stravensky Térence (Parasit Vectors, 2018)
BACKGROUND: Members of the Anopheles gambiae (s.l.) complex are one of the major vectors of malaria in Africa. LLINs and IRS are the most effective tools used in vector control of malaria. However, their effectiveness may be hampered by the development and spread of insecticide resistance in the target vectors species. The objective of this study was to assess the susceptibility of Anopheles gambiae (s.l.) mosquitoes from South-West Cameroon to deltamethrin, permethrin and to malathion, four years after the mass deployment of LLINs. METHODS: Anopheles larvae were collected from Limbe, Tiko and Buea, three cities of the Fako division and reared until adult emergence. Adult mosquitoes from field larvae were identified as belonging to the Anopheles gambiae (s.l.) complex using standard identification keys. Susceptibility of mosquito samples to deltamethrin, permethrin and malathion was assessed using WHO susceptibility tests protocol for adult mosquitoes. Molecular identification of tested samples was performed using the PCR SINE200 protocol and by PCR-RFLP. The kdr alleles were genotyped using the hot ligation oligonucleotide assay (HOLA). RESULTS: Two species of the An. gambiae (s.l.) complex, An. coluzzii and An. gambiae (s.s.) were identified in all three study locations with high proportions of An. coluzzii in Limbe (84.06%) and Tiko (92.2%), while in Buea, An. coluzzii (55.6%) and An. gambiae (s.s.) (44.4%) occurred almost in the same proportions. Tested samples were found resistant to pyrethroids (deltamethrin and permethrin) in all locations (< 90% mortality), with > 3-fold increase of KDT(50) values compared with the Kisumu susceptible reference strain of An. gambiae (s.s.). However, the mosquito populations from Limbe and Buea were fully susceptible to malathion. The L1014F kdr was found in both An. coluzzii and An. gambiae (s.s.) with the highest frequencies found in An. gambiae (s.l.) populations from Tiko (94%) and Buea (90%) compared with the Limbe population (66%) (P = 0.00063, df = 2). No kdr L1014S was observed in analyzed samples. CONCLUSIONS: These findings reemphasize the ongoing development of An. gambiae (s.l.) resistance to pyrethroids used in impregnating LLINs and suggest the use of malathion as an alternative insecticide for IRS in complementarity with LLINs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13071-018-2979-1) contains supplementary material, which is available to authorized users.